2005
DOI: 10.1038/sj.jhh.1001925
|View full text |Cite
|
Sign up to set email alerts
|

Influence of childhood socioeconomic circumstances, height, and obesity on pulse pressure and systolic and diastolic blood pressure in older people

Abstract: This study assesses the association of childhood socioeconomic circumstances, height, and obesity with components of blood pressure. We selected 4009 people representative of the Spanish population aged 60 years and older, and estimated systolic blood pressure (SBP), diastolic blood pressure (DBP), and pulse pressure (PP) according to childhood social class, height, and obesity. No association was found between childhood social class and blood pressure. SBP showed an inverse gradient and DBP a direct gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Various hypotheses, such as vessel size, socioeconomic status and greater central pressure augmentation, have been suggested to explain these associations (20)(21)(22)(23)(24). A recent study in 558 patients with nonvalvular atrial fibrillation and preserved left ventricular systolic function found that short stature, left atrial size and E/E' were independent predictors of stroke.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Various hypotheses, such as vessel size, socioeconomic status and greater central pressure augmentation, have been suggested to explain these associations (20)(21)(22)(23)(24). A recent study in 558 patients with nonvalvular atrial fibrillation and preserved left ventricular systolic function found that short stature, left atrial size and E/E' were independent predictors of stroke.…”
Section: Discussionmentioning
confidence: 93%
“…Several previous studies have observed a relationship between shorter height and the risk of cardiovascular diseases and mortality (20)(21)(22)(23)(24). Various hypotheses, such as vessel size, socioeconomic status and greater central pressure augmentation, have been suggested to explain these associations (20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 95%
“…Although some studies have shown the correlations between high blood pressure or high prevalence of hypertension and low SES in different population groups, such as Swiss [30], American [31], French [32], Israel [6], Chinese [33] or Thai [34], other epidemiologic studies with no association [35,36] or conflicting results [37,38] were also reported. Our observation provided new evidence supporting the negative association between SES and blood pressure or prevalence of hypertension by using our Japanese occupational cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have observed that adverse childhood socioeconomic circumstances and short stature increase the risk of coronary heart disease [14], while others [15] found obesity in adulthood to be a determining factor of adult blood pressure, independent of socioeconomic circumstances in childhood. This therefore suggests that adverse environmental conditions in early life responsible for childhood malnutrition that improves later on may be equally responsible for the cause of obesity in adulthood, which in turn may make adults more susceptible to cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%